Utility of interim apparent diffusion coefficient value in predicting treatment response among patients with locally advanced cervical cancer treated with radiotherapy - Liang, Chunyu; Wang, Wei; Yang, Guohui; Xu, Zhiyuan; Li, Jian; Wu, Kusheng; Shen, Xinping (Clinical and translational radiation oncology, 2024)
•This research investigated the utility of pre-treatment, interim-ADC as well as change in ADC for predicting treatment outcomes in patients with cervical carcinoma treated with radiotherapy.•Multivariate logistic regression revealed that the baseline tumor diameter and interim-ADC were significant prognostic factors for treatment response.•Interim-ADC value may serve as a novel imaging marker for predicting the outcomes of therapy. For locally advanced cervical cancer (LACC), treatment response to radiotherapy (RT) can vary significantly even among those with the same stage classification of International Federation of Gynecology and Obstetrics (FIGO). This study investigated the value of ADC metric for forecasting end-of-treatment outcomes in LACC patients referred for RT. Eighty patients with pathologically confirmed cervical squamous cell carcinoma with (SCC) were included in the research. Abdominal or pelvic MRI scans were conducted at least three times for all participants: before RT, three weeks after beginning of RT and approximately two months after RT was finalized. Calculated apparent diffusion coefficient (ADC) values of the LACC include: pre-ADC, interim-ADC, ΔADC and Δ%ADC. Based on Response Evaluation Criteria in Solid Tumors (RECIST) 1.1,subjects were calculated and subsequently categorized into good responders group (complete response) and poor responders group (progressive disease, stable disease or partial response). Compared to good-responders, subjects of poor-responder group showed significantly lower values of interim-ADC, ΔADC, and Δ%ADC (all P < 0.05). To distinguish between good and poor responders, the optimal cutoff values of interim-ADC, ΔADC, and Δ%ADC were determined to be 1.067 × 10−3 mm2/sec, 0.209 × 10−3 mm2/sec, and 30.74 % using the ROC curve, with corresponding sensitivities of 83.78 %, 86.49 %, 75.68 %, and specificities of 88.37 %, 86.49 %, 75.68 %, respectively. Multivariate logistic regression revealed that the baseline tumor diameter and interim-ADC were significant prognostic factors for treatment response with an odds ratio (OR) of 0.105 (95 % confidence interval [95 % CI] 0.018–0.616) for baseline tumor diameter and 42.896 (95 % CI 8.205–224.262) for interim-ADC. The interim-ADC value and baseline tumor diameter surfaced as possible indicative factors for predicting the response to RT in patients with LACC.